Primary and high schools teachers' perceptions of organizational citizenship (Malatya province sample) - Korkmaz, Celalettin; Arabaci, I. Bakir (Ankara University, 2013)
This research aims to determine the perceptions of organizational citizenship of primary and high schools teachers working in Malatya. The sample of the study constituted 927 teachers. As a means of data collection, OCB scale is developed by using as a base of first OCB scale, developed by Podsakoff and McKanzie with regard to Organ's 5 dimensions and by making use of other studies in literature. According to the findings of the research, statistically significant differences have been revealed among staffed, contracted, paid teachers, between teachers working in public and private schools, between city center and town center with village/rural area schools teachers and between primary and secondary schools teachers.
İlkö?retim ve ortaö?retim okulları ö?retmenlerinin örgütsel vatandaşlık algıları (Malatya İli örne?i)
Keywords: Organizational citizenship behaviour; Primary and secondary schools; Teacher